2010
DOI: 10.1038/npp.2010.69
|View full text |Cite
|
Sign up to set email alerts
|

Reboxetine Enhances the Olanzapine-Induced Antipsychotic-Like Effect, Cortical Dopamine Outflow and NMDA Receptor-Mediated Transmission

Abstract: Preclinical data have shown that addition of the selective norepinephrine transporter (NET) inhibitor reboxetine increases the antipsychotic-like effect of the D 2/3 antagonist raclopride and, in parallel, enhances cortical dopamine output. Subsequent clinical results suggested that adding reboxetine to stable treatments with various antipsychotic drugs (APDs) may improve positive, negative and depressive symptoms in schizophrenia. In this study, we investigated in rats the effects of adding reboxetine to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 78 publications
2
4
0
Order By: Relevance
“…Moreover, in this model, the addition of IDAZ enhanced the antipsychotic effects of risperidone, facilitated dopaminergic and glutamatergic neurotransmission, and allowed a lower dose of risperidone to achieve maximal effect (Marcus et al, 2010b). Consistent with the findings here, the addition of the NE reuptake inhibitor, reboxetine, to olanzapine (another atypical antipsychotic) also enhanced olanzapine's antipsychotic effects as well as glutamatergic and dopaminergic neurotransmission (Marcus et al, 2010a). Since CLOZ can also directly modulate glutamatergic circuitry (Heresco-Levy, 2003), we will explore the potential role of these mechanisms in mediating CLOZ's effects on alcohol drinking future studies, as well as the potential combination of ILOP with glutamatergic agents to achieve a CLOZ-like effect.…”
Section: Discussionsupporting
confidence: 80%
“…Moreover, in this model, the addition of IDAZ enhanced the antipsychotic effects of risperidone, facilitated dopaminergic and glutamatergic neurotransmission, and allowed a lower dose of risperidone to achieve maximal effect (Marcus et al, 2010b). Consistent with the findings here, the addition of the NE reuptake inhibitor, reboxetine, to olanzapine (another atypical antipsychotic) also enhanced olanzapine's antipsychotic effects as well as glutamatergic and dopaminergic neurotransmission (Marcus et al, 2010a). Since CLOZ can also directly modulate glutamatergic circuitry (Heresco-Levy, 2003), we will explore the potential role of these mechanisms in mediating CLOZ's effects on alcohol drinking future studies, as well as the potential combination of ILOP with glutamatergic agents to achieve a CLOZ-like effect.…”
Section: Discussionsupporting
confidence: 80%
“…Specifically, augmentation with antidepressants has been shown to improve the efficacy of antipsychotics for positive (Joffe et al, 2009;Terevnikov et al, 2010;Terevnikov et al, 2011), negative (Raedler et al, 2004;Singh et al, 2010) and cognitive symptoms (Stenberg et al, 2010;Vernon et al, 2014). Although a double blind placebo-controlled study could not confirm these effects (Usall et al, 2014), observations linking the beneficial effects of monoamine releasers co-administered with antipsychotics are largely in line with data obtained using animal models (Bjorkholm et al, 2015;Marcus et al, 2010;Marcus et al, 2012).…”
Section: ) Augmentation Is Used To Counteract Antipsychotic Failurementioning
confidence: 62%
“…RB has been shown to increase the burst‐firing pattern of ventral tegmentum area DA neurons and to increase DA release in the prefrontal cortex (Linner et al, ). Recent studies also showed increased DA outflow in the prefrontal cortex and other regions after treatment with RB (Marcus et al, ; Masana et al, ).…”
Section: Discussionmentioning
confidence: 93%